The Economics of Ecosystem Restoration (TEER): Database of costs and benefits of restoration. - CGIAR Research Program on Forests, Trees and Agroforestry (2019)
Tables standardizing description of interventions, contexts and costs as well as template for data collection finalized and agreed with partners. To be pilot tested in coming months. Structure and functionalities of data base described.